Orchids and orchidology in Central America. 500 years of history - Ossenbach, Carlos (Universidad de Costa Rica, 2013)
The idea for this book was proposed by Dr. Joseph Arditti during the 1st. International Conference on Neotropical Orchidology that was held in San José, Costa Rica, in May 2003. In its first chapters, this is without doubt a history of orchids, relating the role they played in the life of our ancient indigenous people and later in that of the Spanish conquerors, and the ornamental, medicinal and economical uses they gave to these plants. It is not until the late XVIII century, but above all in the XIX century that we can talk about a history of orchidology, with the development of botanical science and the establishment of the bases of modern orchidology by Lindley. But the XIX century was also the time of legendary commercial collectors who, frequently with the complicity of men of science, collected with a frenzy often bordering on madness. Orchid knowledge became sometimes a synonym of orchid destruction. During the second half of the XX century the world developed a growing conscience of the negative impact of man on his natural habitat and I would like to believe that, in the future, orchidology will devote itself in an increasing manner to the study of orchids as a means to preserve them. Motivated by this belief, I decided to write this history, that will be more a story about orchids and men than a story about orchids and science, hoping that mankind will rediscover the harmonious relation with nature that characterized the life of the first inhabitants of our region. The great naturalist Alexander F. Skutch, who chose a life of study and contemplation amidst the forests of southern Costa Rica, expressed it in much better words: “Sometimes, before leaving the hilltop, I visit the old Indian burial ground. Despite promises of golden ornaments, I have never permitted anyone to excavate these graves, for I believe that we should treat the burials of alien races with the same respect that we desire for our own. Sometimes, in a meditative mood, I ask myself whether, from the moral standpoint, my title to this land is as valid as that of the men whose dust lies beneath the red clay. Perhaps the only answer to this perplexing question is that he most deserves to have the land who makes the best use of it. If my love of the mountains and rivers and forests is greater than theirs, if these things speak more meaningfully to me and I am more keenly appreciative of their beauty; if I strive harder to preserve this natural setting in its pristine splendor and to conserve the soil’s fertility — then perhaps I can justify my possession of this land that once belonged to them. If I fall short of the aborigines in these respects, then I — and the whole line of too-aggressive palefaces who transmitted to me what was once theirs — are but piratical intruders, whose right to this land would be hard to defend. Enlarging on this theme, it seems to me that, unless evolution miscarries, the ultimate possessor of the earth will be the race that most appreciates its grandeur and beauty and cherishes it most carefully, that rules it as a generous and compassionate lord instead of raping it like a greedy tyrant, as men have all too commonly done” (Skutch, 1971: 223-224).